Comparative Inter- and IntraSpecies Transcriptomics Revealed Key Differential Pathways Associated With Aluminium Stress Tolerance in Lentil - Singh, Chandan Kumar; Singh, Dharmendra; Taunk, Jyoti; Chaudhary, Priya; Tomar, Ram Sewak Singh; Chandra, Shivani; Singh, Deepti; Pal, Madan; Konjengbam, Noren Singh; Singh, M. Premjit; Singh Sengar, Rakesh; Sarker, Ashutosh (Frontiers in Plant Science, 2021)
Aluminium (Al) stress circumstances plant growth retardation and engenders productivity loss under acidic soils. Present study accentuates morpho-physiological, and molecular bases of Al tolerance within and between wild (ILWL-15) and cultivated (L-4602 and BM-4) lentil species. Morpho-physiological studies revealed better cyto-morphology of tolerant genotypes over sensitive under Al stress. Mitotic lesions were observed in root cells under these conditions. Transcriptome analysis under Al stress revealed 30,158 specifically up-regulated genes in different comparison groups showing contigs between 15,305 to 18,861 bp. In tolerant genotypes, top up-regulated Differentially Expressed Genes (DEGs) were found to be involved in organic acid synthesis and exudation, production of antioxidants, callose synthesis, protein degradation along with phytohormone and calcium mediated signalling under stress condition. DEGs associated with epigenetic regulation and Al sequestration inside vacuole were specifically upregulated in wild and cultivars, respectively. . Based on assembled unigenes, average of 6645.7 Simple Sequence Repeats and 14953.7 high-quality Single Nucleotide Polymorphisms were spotted. Using quantitative Real Time-Polymerase Chain Reaction, twelve selected genes were validated. Gene Ontology (GO) annotation revealed a total of 8,757 GO terms in three categories viz .molecular, biological, and cellular processes. Kyoto Encyclopaedia of Genes and Genomes pathway scanning also revealed another probable pathway pertaining to metacaspase-1, 4, and 9 for programmed cell death under Al-stress condition. This investigation reveals key inter- and intra-species metabolic pathways associated with Al-stress tolerance in lentil species which can be utilized in designing future breeding programmes to improve lentil and related species towards Al stress.